Exploring the potential of tiger milk mushroom (Lignosus rhinocerotis) crude extracts as immunostimulants for Pacific white shrimp (Litopenaeus vannamei): effects on survival and immunological responses against Vibrio parahaemolyticus - Pung, Qi En; Chen, Yan; Chong, Chou Min; Lee, Po Tsang; Peng, Kai; Liew, Hon Jung; Loh, Jiun Yan (Taylor and Francis, 2025)
This study investigated the effects of tiger milk mushroom (Lignosus rhinocerotis) extract (LRE) on immune responses and resistance against the aquatic pathogen Vibrio parahaemolyticus in Pacific white shrimp (Litopenaeus vannamei) to improve disease management in shrimp aquaculture. LREs were extracted using methanol and water to evaluate their cytotoxicity and antimicrobial efficacy. L. rhinocerotis methanol extract (LRME) exhibited higher antimicrobial activity and lower acute toxicity compared to the aqueous extract, and was selected for subsequent in vitro hemocyte assays and in vivo feeding trials. The in vivo trials were conducted in two batches, with each batch consisting of five diets: a basal diet without LRME inclusion (control), a commercial diet, and three treatment diets supplemented with LRME at 1 g (LRME1), 5 g (LRME5), and 10 g (LRME10) per kilogram of feed. Each diet had three replicates (n = 3). The first batch included 120 shrimp with an average weight of 13.38 ± 1.72 g, and was used to evaluate immune parameters, including total hemocyte count (THC), hemocyte type proportions, phenoloxidase (PO) activity, phagocytic activity, and reactive oxygen species (ROS) production, over a 12-day feeding trial. The second batch consisted of 225 post-larvae (PL10) with an average weight of 0.06 ± 0.01 g, and was used for bacterial challenge tests to assess survival rates following a 4-day feeding trial. In the 12-day feeding trial, shrimp fed with LRME showed significant increases in THC, ROS production, phagocytic, and PO activity, with LRME1 consistently demonstrating substantial improvements across multiple immune parameters. Days 4 and 8 were observed as specific time points when LRME exhibited significant effects on shrimp immunity, highlighting the temporal nature of shrimp immune responses to LRME supplementation. In a subsequent bacterial challenge test, a 4-day supplementation of LRME1 significantly enhanced shrimp survival rates. This study highlights the potential of LRME in enhancing shrimp immunity and resistance against V. parahaemolyticus, with significant effects observed at 1 g kg−1 dietary inclusion and a supplementation period of 4 days.